The Role of Regional Cultural Week in an Effort to Maintain the Existence of Traditional Games as the Nation's Cultural Heritage in the Modern Era - Bambang Yuniarto; Ibnu Umar Fahdri; Aldi Salam; Ade Nur; Aliya Masrurah (Journal of Social Research, 2023)
In writing this journal will be discussed on the topic entitled "The Role of Regional Cultural Week in an Effort to Care for the Existence of Traditional Games as the Nation's Cultural Heritage in the Modern Era" to explore the topic, the Government should make efforts to carry out activities or events every year or every month that invite the nation's generation and children to be more familiar with traditional games in the modern era so that in these efforts traditional games will not Completely lost, besides that, the government must also work with parents so that their children are limited in the use of gadgets because with children who are not limited in the use of gadgets, there will be a dislike for traditional games, parents must also invite their children in every cultural week event based on traditional games to maintain the existence of cultural heritage. Efforts to maintain the existence of traditional games can be applied through books, holding traditional game activities at school or at home, building communities in the community and others. This research methodology uses a qualitative approach and the system used in this scientific work is a descriptive method. Literature research is research conducted where the author collects data and collects data from various sources. The sources taken are among others from books, and websites. On the other hand, library research is used as the first step of research to determine the research topic, with the conduct of this research will be used as material for further research and analysis to obtain research results. Where the most important thought of the discussion is to provide knowledge and increase broader insight.